Design of a Smart Barrier to Internal Flooding - Jorge Muñoz-Caballero; Diego Vergara; Pablo Fernández-Arias; Álvaro Antón-Sancho (Inventions, 2022)
Increasingly, and with greater frequency, humanity is experiencing violent weather storms, which cause innumerable human and economic losses. Among the most frequent climatic storms that cause considerable losses are floods. Usually, domestic anti-flood systems are not autonomous; they require human intervention. This article presents Smart Flood Barrier (SFB), which is a fully automated system using sensors and composed of hinged lintels that can be installed on any door of any commercial brand. SFB is responsible for diverting the flow of fluid towards the center of a street with a certain slope, generating a “dry zone” near the entrance door to the house. This device also has a barrier installed in front of the door, which will be responsible for hermetically sealing the lintels, preventing the passage into the interior of the house if it is possible for the fluid to flow in the opposite direction to the direction of fluid flow.